Legal Measures on Crop Insurance - Tejangkura, Nabhasrabi; Sutthibodee, Panya (Muban Chombueng Rajabhat University Research Journal (Humanities and Social Science), 2020)
The objective of the research was to study legal measures on crop insurance by studying the problems, the theoretical concepts, and foreign laws comparison in order to seek answers in accordance with the defined conceptual framework. The data were collected from 24 in-depth interviews, and a focus group discussion of 30 participants divided into 3 groups. The researcher summarized the data analysis results sequentially according to the objectives. The results were discovered that the population’s occupations in the agricultural sector significantly contributed to the economy of the country, while the crops they grew depended on the weather and natural disasters, which were uncontrollable risks, which affecting agriculturists in terms of productivity, losses, and household debts, as well as, stability in their occupations and the economy of the country. Thailand lacks the appropriate legal measures on crop insurance, which is an important instrument in managing risks from natural disasters to reduce potential risks, or as a remedy for disaster damage. In comparison with foreign laws, Thailand should establish comprehensive and sustainable legal provisions on crop insurance, for example, it should provide, for instance, the objects of insurance, the types of insurance, the qualifications of the insured, and the premium rate determination, so that agriculturists are able to access to crop insurance of Thailand systematically, and to manage risks concretely, which would benefit the country's economic system.